Mies and modern living - Reuter, Helmut; Schulte, Birgit; Rohe, Mies van der. ([S.l.] : Hatje Cantz, 2009)
In 1929 Barcelona was host to the World Arts Fair, an international architecture and design exposition attended by members of the Spanish royalty and many senior European government officials. It was an occasion for cultural grandstanding, an opportunity for countries to parade their native talent. So when the German government approached Ludwig Mies van der Rohe (1886-1969) to design a pavilion, he was left in no doubt as to their expectations--and he met them, erecting an ultra-modern creation in glass, steel and four types of marble. Once he had accomplished this, Mies then set about designing furniture for his building--something none of his competitors appear to have thought of. Thus was born the iconic Barcelona chair, an ingenious blend of clean Modernist steel tubing and comfort-appeal cushioning. Gathering the proceedings of a 2007 symposium on van der Rohe, this publication takes the Barcelona chair as a starting point to address his progressive ideas on interior space and continuities between architecture and furniture design. Experts trace the highlights of Mies' career and flesh out a context for his innovations in the ferment of 1920s and 1930s Berlin. Also included is a series of previously unpublished photographs of Mies' work. Author of the proto-Minimalist aphorism, "less is more," Ludwig Mies van der Rohe is not only one of the twentieth century's greatest architects, but the creator of numerous milestones in the history of design.